OPERATIONAL ATLAS OF EXPOSED MORTARS AND CONGLOMERATES FOR INTERVENTIONS ON THE WIDESPREAD ARCHITECTURAL HERITAGE - Sara Fasana; Marco Zerbinatti; Alessandro Grazzini; Federico Vecchio (Tema, 2020)
When it comes to Science Heritage, the availability of refined investigation techniques, advanced knowledge of the characteristics of materials, the current technological capacity and the synergy of specialised operators, coordinated into multidisciplinary teams, guarantee, with the support of cutting-edge tools, excellent results for every conservative operation applied to monumental buildings of acknowledged interest. On the contrary, there are still strong limits to the likelihood that this excellence will reverberate on the multitude of interventions performed on widespread architectural heritage. The research project underway envisages the preparation of an operational atlas of reference for exposed mortars and conglomerates, based on the historical and technological knowledge of materials (particularly those available locally) complete with experimental data on constitution and performance, which is useful to support the development of compatible maintenance and conservation procedures.